2023
DOI: 10.3389/fpubh.2023.1076879
|View full text |Cite
|
Sign up to set email alerts
|

Mapping study of papillary thyroid carcinoma in China: Predicting EQ-5D-5L utility values from FACT-H&N

Abstract: ObjectiveTo develop a mapping algorithm that can be used to predict EQ-5D-5L health utility scores from FACT-H&N and obtain health utility parameters for Chinese patients with papillary thyroid carcinoma (PTC), which can be used for cost-utility analysis in health economic.MethodsA total of 1,050 patients with PTC from a tertiary hospital in China were included, and they completed FACT-H&N and EQ-5D-5L. Four mapping algorithms of direct mapping functions were used to derive the models: Ordinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
1
2
Order By: Relevance
“…In this study, SF-6D was used to measure the health utility value of thyroid cancer. It was found that only 0.286% of patients had ceiling effect, which was lower than the results obtained by our research group using the EQ-5D-5L scale (9.62%) ( 16 ), and also lower than the ceiling effect of the EQ-5D-5L scale used in the breast cancer study (3.85%) ( 36 ). This may be because SF-6D has more states than EQ-5D.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In this study, SF-6D was used to measure the health utility value of thyroid cancer. It was found that only 0.286% of patients had ceiling effect, which was lower than the results obtained by our research group using the EQ-5D-5L scale (9.62%) ( 16 ), and also lower than the ceiling effect of the EQ-5D-5L scale used in the breast cancer study (3.85%) ( 36 ). This may be because SF-6D has more states than EQ-5D.…”
Section: Discussioncontrasting
confidence: 77%
“…Although there are studies on mapping FACT-B to SF-6D in breast cancer patients ( 14 ), and mapping FACT-G and FACT-C to SF-6D in colorectal cancer patients ( 15 ). However, apart from a mapping study from FACT-H&N to EQ-5D-5L published by our research group ( 16 ), we did not find any other mapping studies in thyroid cancer patients. To our knowledge, no study has mapped FACT-H&N scores to SF-6D utility scores using direct or indirect methods in thyroid cancer samples thus far.…”
Section: Introductioncontrasting
confidence: 78%
“…Xu et al formulated algorithms to map the EORTC QLQ-C30 (QLQ-C30) onto EQ-5D-5L within a patient sample diagnosed with lymphomas[30]. More mapping algorithms were developed including psoriasis disability index, Haem-A-QoL scores, Parkinson’s Disease Questionnaire[6; 12; 29].…”
Section: Discussionmentioning
confidence: 99%